2003
DOI: 10.1148/radiol.2282020798
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Septal Defects in Pediatric Patients: Noninvasive Sizing with Cardiovascular MR Imaging

Abstract: In children with ASD and inconclusive TTE results, MR imaging can enable determination of defect size, rim distances to adjacent structures, and venous connections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Other noninvasive methods have also been studied; Durongpisitkul et al [8] suggested using MRI for accurate sizing [9], whereas Zhu et al[ 10] suggested using 3-dimensional measurement giving excellent correlation. Intracardiac echo provides accurate measurement as well and allows the procedure to be carried out without anesthesia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other noninvasive methods have also been studied; Durongpisitkul et al [8] suggested using MRI for accurate sizing [9], whereas Zhu et al[ 10] suggested using 3-dimensional measurement giving excellent correlation. Intracardiac echo provides accurate measurement as well and allows the procedure to be carried out without anesthesia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac output, pulmonaryto-systemic fl ow ratio and quantifi cation of gradients across stenoses and valvar regurgitation can all be accurately determined using this technique. Volume blood fl ow measured using this technique has been shown to be accurate when compared to both invasive oximetry (10) and fl ow-phantom experiments. (10) In the case of stenoses interrogation, excellent comparative data exists with Doppler echocardiography and catheter data.…”
Section: Specifi C Imaging Techniquesmentioning
confidence: 96%
“…Volume blood fl ow measured using this technique has been shown to be accurate when compared to both invasive oximetry (10) and fl ow-phantom experiments. (10) In the case of stenoses interrogation, excellent comparative data exists with Doppler echocardiography and catheter data. (11) The quantifi cation of regurgitant volume using this technique has been demonstrated to be superior to echocardiography.…”
Section: Specifi C Imaging Techniquesmentioning
confidence: 96%
See 2 more Smart Citations